Dialysis Center Business Plan: Design Thinking Marketing Strategy In Haemodialysis Services - Heydi Marizky Lisman; Prastuti Soewondo; Novita Dwi Istanti; Muhammad Hafiz Aini (Syntax Corporation Indonesia, 2023)
Chronic kidney disease (CKD) is an important public and medical problem in the world because of the huge burden on the health care system. The prevalence of CKD has increased dramatically in the last three decades The study was conducted at the RS X Dialysis Unit in February-March 2023. This research is a descriptive-analytical research. The type of data used is primary data and secondary data. The primary data used are the results of interviews. Identify internal factors based on indicators of strengths and weaknesses. The identification process aims to assess and evaluate the internal strategic factors that influence the success of hemodialysis services. Internal factors used in research based on the state of the Dialysis Unit in terms of management, marketing, research and development and information systems. The position of hemodialysis services at the Dialysis Unit of RS X Depok City is in a growth position. From the results of data processing using QSPM, alternative strategies are obtained, namely maintaining good service quality and facilities, increasing service time in accordance with the target achievement per day which is aligned with the availability of human resources, opening services for infectious spaces open for outpatients, utilizing Social Media for access socialization when the main access is closed during holidays, social media intervention in the marketing process related to the convenience of doing HD in RS X Depok City and education related to PGK-HD, make the HD RS X Depok City patient community a forum for sharing and educating patients and increasing the ease of access and HD facilities at RS X Depok City.